CONVERGENCE CITIZENS: THE NEW MEDIA LITERACY OF PRE-SCHOOL TELEVISION. - Shore, Amy (Afterimage)
The article discusses innovations in media literacy of pre-school television. The author gives an in-depth examination of the role of the pioneering educational television program "Sesame Street" in encouraging children to become active users of media rather than passive consumers of interactive programming models. It is noted that "Sesame Street" had a profound influence on children's media including the popular program for preschoolers called "Dora the Explorer."